Psychometric properties of the revised Spanish version of the German test anxiety inventory (GTAI-AR) in Argentinean university students - Piemontesi, Sebastián Eduardo; Universidad Nacional de Córdoba (Pontificia Universidad Javeriana, 2011)
In the present study was evaluated the psychometric properties of the Spanish version of the German Test Anxiety Inventory in argentinean university students. Was conducted an exploratory and confirmatory factor analysis using items parcels. Was evaluated the fit of three possible models according to the theoretical background, one that supports the unidimensionality of the test anxiety, other that distinguishes the cognitive and affective components, and one that comprising four dimensions, worry, interference, lack of confidence and emotionality like primary factors and total test anxiety like secondary factor. Fit indices for the last model were all adequate. Are discussed the results, the use of items parcels and the importance of multidimensional instruments of test anxiety in Spanish language